2018
DOI: 10.1155/2018/7681039
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Prognosis of Prostate Cancer from Circulating Matrix Metalloproteinases and Inhibitors

Abstract: Although prostate cancer (PCa) is the sixth most common type of neoplasm in the world and the second in prevalence among men (10% of all cases), there is shortage of studies focused on primary prevention of the disorder as well as little understanding on its pathophysiology. Currently, the PCa screening tools are the prostate specific antigen (PSA) dosage conjugated to rectal examination and confirmed by prostate biopsy. Despite the name, the PSA presents reduced specificity, being necessary the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The role of specific MMPs and ADAMs in breast [6,72,73], lung [74][75][76][77], prostate [78][79][80], and colorecta [81] cancer progression, invasion, and metastasis has been studied extensively [18,49,82]. MPs carry a multifaceted role in cancer and they can act as a pro-tumorigenic, anti-tumorigenic, or null factor [6], making it difficult to draw a general conclusion on the role of all MPs without considering all the parameters involved in the model of study such as the individual genomic profile, proteomic profile, and experimental conditions.…”
Section: Mps In Cancermentioning
confidence: 99%
“…The role of specific MMPs and ADAMs in breast [6,72,73], lung [74][75][76][77], prostate [78][79][80], and colorecta [81] cancer progression, invasion, and metastasis has been studied extensively [18,49,82]. MPs carry a multifaceted role in cancer and they can act as a pro-tumorigenic, anti-tumorigenic, or null factor [6], making it difficult to draw a general conclusion on the role of all MPs without considering all the parameters involved in the model of study such as the individual genomic profile, proteomic profile, and experimental conditions.…”
Section: Mps In Cancermentioning
confidence: 99%
“…The prognosis of PC is also associated with age, with older age being the bestestablished risk factor. Studies indicate that both incidence and mortality increase after age 50, with three-quarters of new cases around age 65 2,16 . In this context, we observed that 56% of the patients with PA in our study were between 60 and 69 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Serum PSA is measured for early detection, staging, and monitoring of the disease. However, it might have low specificity when the values range between 3 and 10 ng/ml, and also showing an increase in benign conditions such as BHP and prostatitis 2,16 . The search for new biomarkers, which combined with PSA can provide greater precision in the diagnosis, has led to several studies on the expression of MMP, both in serum and in tissue samples of PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that the class of serum proteinases of matrix metalloproteinase (MMP) nature is importantly involved in PCa, with potential utility for the entity's diagnosis [8]. MMPs are zinc-and calcium-dependent endopeptidases that degrade various elements of the extracellular matrix (ECM), especially collagen, elastin, laminin, fibronectin, and proteoglycans, and take part in physiological processes involving tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%